LOCAL MATERIAL TESTING FOR PAVEMENT MATERIAL ON REMOTE AND OUTMOST ISLAND - Iwan Susanto; Nono Nono (Pusbindiklat - LIPI, 2018)
Road infrastructure development in remote and outmost islands such as Mentawai, Aru, and Morotai faced a problem i.e. dificulty in the availability of standard material. The standard material had to be transported from other areas that taking a long time and high cost of transportation. In fact, the three islands had abundant materials. However, there was no study conducted to examine the properties of the local material. The study aim was to find out the physical properties of pavement material that will be the basis of pavement design. The research began with the selection of material, discussion with experts, coordination with involved parties, site observation, and laboratory test. The analysis of testing result used comparative analysis that compared test result to certain standard. Based on the analysis, local material from Mentawai Islands was suitable for foundation layer with cement stabilization 6%. Coral from Aru Island and limestone from Momojiu Morotai Island could also be utilized for foundation layer. Limestone from Rau Morotai Island utilized for aspalt mixture. Sand from Aru Island and sea sand from Morotai Island could be used for aspalt mixture and concrete cement mixture.